The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1017/s0022215106002052
|View full text |Cite
|
Sign up to set email alerts
|

Spinal accessory nerve function after neck dissections

Abstract: The aim of this study was to evaluate spinal accessory nerve function after functional neck dissection (FND) and radical neck dissection (RND) by monitoring the nerve with electromyographic (EMG) examinations. A prospective, double-blind, clinical study was undertaken in 21 patients (42 neck side dissections) operated on for head and neck malignant diseases, separated into two groups: 10 neck sides in the RND group and 32 neck sides in the FND group. Electromyographic examinations were performed pre-operativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
2
29
0
2
Order By: Relevance
“…These findings are in agreement with those from our study 15 . We have noticed that Snd causes better shoulder function when compared to other types of dissections; this difference has been explained by less level V manipulation during the surgical procedure, resulting in less damage to the accessory nerve and the neck plexus 1,7,[12][13][14]17,18 . The shoulder syndrome is an important sequela of nd.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These findings are in agreement with those from our study 15 . We have noticed that Snd causes better shoulder function when compared to other types of dissections; this difference has been explained by less level V manipulation during the surgical procedure, resulting in less damage to the accessory nerve and the neck plexus 1,7,[12][13][14]17,18 . The shoulder syndrome is an important sequela of nd.…”
Section: Discussionmentioning
confidence: 95%
“…electrophysiological evaluations have shown that, despite the nerve's anatomical integrity, the risk is even greater whenever the neck's posterior triangle is involved (level V) 1,[15][16][17] . The muscles' denervation potentials become characteristic after two to three weeks of the lesion, first on the proximal muscles, later on the distal ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional outcomes following RND are inferior to spinal accessory nerve-sparing procedures due to the resultant chronic trapezius dysfunction. 7,9,13,33,43,50,53 The MRND and SND procedures were developed to spare the spinal accessory nerve, thus limit trapezius dysfunction; however, significant incidence of spinal accessory nerve injury has been reported 6,10,13,14,52,53 that might have resulted from nerve manipulation. 6,29,43,50,52 The MRND requires lymph node dissection at all levels, but the spinal accessory nerve is usually spared.…”
Section: Case Series Descriptionmentioning
confidence: 99%
“…40 Spinal accessory nerve injury commonly occurs during neck dissection surgery. 2,6,9,11,[13][14][15][27][28][29]31,43,46,48,49,52,53 Neck dissection surgery is performed to treat head and neck carcinoma and is categorized into 3 different procedures: radical S pinal accessory nerve palsy (SANP) is common following neck dissection surgery or lymph node excision, 2,6,9,11,[13][14][15][27][28][29]31,43,46,48,49,52,53 blunt or penetrating trauma to the lateral neck region, 2,11 and cervical stretch injuries. 32 Spinal accessory nerve injury results in trapezius paralysis or dysfunction and a diagnostic cluster of signs and symptoms, including shoulder girdle depression, trapezius atrophy, scapular dyskinesis, loss of shoulder STUDY DESIGN: Retrospective case series.…”
mentioning
confidence: 99%